BIOCONVERSION OF PHYTOSTEROL TO ANDROSTENEDIONE (AD) BY STRAIN MYCOBA CTERIUM NEOAURUM - Quý, Nguyễn Thị (Vietnam Journal of Biotechnology, 2011)
Bioconversion of phytosterol, which has a purity of 93%, to androstenedione (AD) by Mycobacterium neoaurum was conducted in 150 milliliters of transformation media in 750 milliliter conical flasks and a five liter fermentor with 3.5 liters of transformation medium. The amount of phytosterol substrate in the transformation media was 1 percent. The culture seed was fed into the transformation media with a ratio of 10 percent. Conversion process in conical flasks was carried out in a rotary shaker at 220 rpm, 30°C, and media pH at 7.5. When the bioconversion process was scaled up in a 5 litter fermentor, the following parameters were maintained: stable temperature at 30°C, agitation speed at 500 rpm, dissolved oxygen content around 80%, pH adjusted to 7.0. The results of all experiments showed that the whole bioconversion period of phytosterol to AD lasted for 96 hours in conical flasks, whereas it was 88 hours in the fermentor. The amount of AD analyzed by thin layer chromatography was 4 grams per liter and its yield output (molar) reached to 73.77% in conical flasks, whereas the result obtained in the fermentor was less than 3 grams per liter according to thin layer hromatography analysis and only 31% (molar) achieved in terms of yield output. The purity of AD products by high performance liquid chromatography (HPLC) was 99.55% and 94.79% in conical flasks and in the fermentor, respectively.